Comparison of the EQ-5D-3L and EQ-5D-5L instruments in patients undergoing unicompartmental knee arthroplasty - Zhipeng Tai; Zhipeng Tai; Dongping Wan; Qiang Zan; Yuanchi Huang; Chao Xu (Frontiers in Medicine)
PurposeThe purpose of this investigation is to assess and contrast the effectiveness of the two EuroQol five dimensions questionnaire (EQ-5D) versions—EQ-5D-3L and EQ-5D-5L—in assessing one-year quality of life outcomes for patients with knee osteoarthritis (KOA) undergoing unicompartmental knee arthroplasty (UKA).Material and methodFrom the medical records at the Honghui Hospital, Xi’an Jiaotong University, 402 individuals aged 50 and above, who were one-year post-operation, were selected to fill out survey questionnaires during their return hospital visits. Of these, 231 respondents (57.5%) completed the questionnaire; 228 completed both versions, and 56 completed the EQ-5D retest questionnaire. The assessment included missing data, ceiling effects, informativity and discriminatory power, as well as response consistency, redistribution properties, and inconsistency. Reliability and validity were also evaluated.ResultsThe results indicate that the EQ-5D-5L surpasses the EQ-5D-3L in construct validity, informativity, detection precision, and discriminatory power. Consistency reliability is also better in the EQ-5D-5L than in the EQ-5D-3L. Both instrument versions maintained reliable levels of test–retest reliability.ConclusionIn patients with KOA undergoing UKA, the EQ-5D-5L has proven superior in measurement capabilities when compared with the EQ-5D-3L one-year post-operation. Thus, it is advised to utilize the EQ-5D-5L for ongoing assessments of quality of life in this specific group of patients.